Analysis of Biogas Production Kinetics from Cow Dung and Food Waste - Puspitasari, Sasikirana; Amanda, Syahla; Prasetyawati, Eka; Syaichurrozi, Iqbal (World Chemical Engineering Journal, 2025)
The increasing volume of organic waste, such as cow dung and food waste, is a significant environmental problem. One potential solution is the utilization of these wastes as raw materials for biogas production through anaerobic processes. This study aims to analyze the rate of biogas production from a mixture of cow dung and food waste with a kinetic approach using three mathematical models: First-Order, Gompertz, and Logistic. The volume of biogas produced was measured periodically and analyzed using the three models to determine kinetic parameters such as the maximum rate of biogas production and time. Using secondary data from previous studies, three kinetic models, namely Gompertz, First Order, and Logistic, were applied to predict biogas. The best modeling results that have been obtained are in Logistic modeling. In this modeling, the SSE value of cow dung is 58.62 mL and potential biogas peoduction is 167.12 mL,  lag phase period is 3.82 mL and maximum biogas production is 15.91 mL.